Persepsi Masyarakat Tetang Keberadaan Videotron di Manahan Surakarta - Bedjo - Sukarno (Exsplorasi, 2011)
ABSTRACTThe existence videotron located in the middle of the highway intersection is assumed to disrupt protokuler Manahan Surakarta public attention at the time of road users to drive a vehicle. studies to test the public perception of videotron has a meaning as a medium of information, education, entertainment or other functions. Formed the perception of the meaning of the stimulus that was caught by humans through three components, namely cognitive, affective and connotative, which is associated with the process of achieving meaning and understanding of a particular object. This study uses qualitative research conducted in a natural situation and triangulation. Inductive data analysis that stresses from these generalizations. The informant understood the meaning of the messages being presented at videotron still monopolized for the benefit of a particular product. In general, public perception of the existence development videotron does notfunction as a source of general knowledge or entertainment.   . Key words: Perception, Meaning and function videotron